2017
DOI: 10.1002/anie.201701006
|View full text |Cite
|
Sign up to set email alerts
|

An Ion‐Responsive Pincer‐Crown Ether Catalyst System for Rapid and Switchable Olefin Isomerization

Abstract: Rapid, selective, and highly controllable iridium-catalyzed allylbenzene isomerization is described, enabled by tunable hemilability based on alkali metal cation binding with a macrocyclic "pincer-crown ether" ligand. An inactive chloride-ligated complex can be activated by halide abstraction with sodium salts, with the resulting catalyst [κ -( NCOP )Ir(H)] exhibiting modest activity. Addition of Li provides a further boost in activity, with up to 1000-fold rate enhancement. Ethers and chloride salts dampen or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Ligands incorporating crown-like moieties to encapsulate alkali or alkaline earth metal ions have been used for many applications, [8] including more recently the promotion of cooperative [9] or cation-responsive catalysts. [10] We recently reported the synthesis and characterization of Co [11] and Fe [12] Schiff base complexes appended by ac rown ether cycle.I n these complexes,t he Co II/I and Fe III/II reduction potentials shift anodically upon incorporation of alkali (up to 120 mV) or alkaline earth metal ions (up to 770 mV). As imilar effect on redox potentials has been observed by incorporation redox-inactive cations in other complexes.…”
mentioning
confidence: 99%
“…Ligands incorporating crown-like moieties to encapsulate alkali or alkaline earth metal ions have been used for many applications, [8] including more recently the promotion of cooperative [9] or cation-responsive catalysts. [10] We recently reported the synthesis and characterization of Co [11] and Fe [12] Schiff base complexes appended by ac rown ether cycle.I n these complexes,t he Co II/I and Fe III/II reduction potentials shift anodically upon incorporation of alkali (up to 120 mV) or alkaline earth metal ions (up to 770 mV). As imilar effect on redox potentials has been observed by incorporation redox-inactive cations in other complexes.…”
mentioning
confidence: 99%
“… 11 Furthermore, cation–macrocycle interactions have been applied for the regulation of stimuli-responsive systems such as gating membranes 12 and fluorescent probes 13 as well as to trigger cation-promoted transformations on metal complexes. 14 Herein, we report the synthesis, characterization, and isomerization behavior of a second generation molecular motor 2 with a crown ether motif integrated in its lower half ( Scheme 2 ). We also demonstrated that the speed of rotation of 2 can be dynamically modulated by reversible coordination of simple alkali and earth alkali metal cations to the crown ether moiety.…”
mentioning
confidence: 99%
“…In an attempted halide abstraction, 1-18c6a was treated with NaBAr F 4 ( Figure 2, Ar F = 3,5bis(trifluoromethyl)phenyl), but a X-ray diffraction study of the resultant crystals revealed a Na + adduct, [k 4 -( 18c6 NCOP iPr )Ir(H)(Cl)@Na][BAr F 4] (1-18c6a@Na, Figure 2), with Na + intercalated by the crown ether and the Clbridging to the Ir center. Similar species were proposed as intermediates in on/off rate-switchable isomerization by the 15-crown-5-based catalyst, 36 although these were not structurally characterized.…”
Section: Synthesis Of New Catalysts Featuring Aza-18-crown-6mentioning
confidence: 84%